Laboratorial Simulation for Assessing the Performance of Slates as Construction Materials in Cold Climates - Fabio Sitzia; Carla Lisci; Vera Pires; Tiago Alves; José Mirão (Applied Sciences, 2023)
This paper presents the results of a laboratory simulation of a subarctic climate carried out in climatic chamber. Realistic daily and seasonal cycles of temperature of a regular subarctic continental climate without dry seasons (Dfc) were simulated and the physical/mechanical properties and performance of the slates were assessed. The slate was selected because of its use as cladding and roofing material in cold regions. Mechanical performances before and after Dfc climate simulation were evaluated through point load index, uniaxial compression, flexural strength and anchor rupture load. A decrease in these mechanical features between 9 and 50% with respect to the initial strengths has been registered. Other physical parameters such as apparent density, open porosity and water absorption were evaluated. The tests showed an increase in open porosity (+72%) and a decrease in bulk density (−0.7%). The results highlighted a predominantly physical decay and mechanical performance decreasing with a relevant lowering in strength without the detection of chemical–mineralogical alterations. Moreover, artificial sun exposure reproduced the weak solar radiation that characterizes the Dfc climate. This was carried out to assess the aesthetic characteristics of the slate, since discoloration under sun exposure was supposed to occur but the slates did not exhibit substantial color changes.